Aqueous biphasic systems for the purification and preservation of biologically active compounds - Quental, Maria João Valente (2020)
Events involving biomolecules with biological activity have a central role in biological processes and functions. Based on their relevance, the development of techniques for their separation/purification without compromising their stability and biological activity is of upmost importance. In this work, aqueous biphasic systems composed of ionic liquids (IL-based ABS) were investigated as alternative techniques for the extraction, purification and preservation of bioactive compounds. The biocompounds investigated comprise antioxidants, amino acids, proteins (including antibodies), and nucleic acids. It is first demonstrated the development of new ABS comprising tetraalkylphosphonium- and tetraalkylammonium-based ILs and carbohydrates or amino acids as salting-out agents. These systems proved to be competitive extraction platforms for antioxidants and aromatic-aliphatic amino acid mixtures when compared to more conventional ABS. Furthermore, it was demonstrated that it is possible to recover the target compounds by a solid-phase extraction step, allowing the IL recycling. In the following set of works, novel ABS for the separation of proteins were considered. Self-buffering ILs of a biological-derived nature were synthesized and used to form ABS to extract bovine serum albumin. In the same line, cholinium-based ILs combined with anions derived from natural acids were combined with a polymer to form ABS to extract antibodies, namely immunoglobulin G (IgG). In both works, the complete extraction of the proteins to the IL-rich phase was achieved in a single step, without compromising the proteins integrity. The last set of works is related with the use of ILs aqueous solutions and IL-based ABS to preserve and extract nucleic acids. It was demonstrated that the RNA integrity and stability are maintained in aqueous solutions of appropriate ILs, and that most ILs at 20 wt% display no cytotoxicity towards human cell lines. Finally, ABS were investigated as integrated extraction-preservation strategies. RNA completely partitions to the IL-rich phase in one-step, which could act as the preservation medium. In both works, RNA was successfully recovered and the IL recycled. Although additional research is still required, the high versatility of IL-based ABS as alternative extraction and preservation media was demonstrated in this thesis, while highlighting their potential to be used in a variety of biotechnological processes.